Religion and Godfatherism as Drivers of Political Dominance: An Empirical Analysis of Nigeria’s Electoral Landscape - Emmanuel Imuede Oyasor (Indonesian Academy of Social and Religious Research (IASRR), 2026)
This study investigates the role of religion and godfatherism in sustaining political dominance in Nigeria, drawing upon survey data from 120 respondents across six geopolitical zones and 45 key informant interviews. The findings reveal that nearly half of respondents acknowledged religious influence on their voting behavior, while over half reported awareness of political godfathers in their communities. Regional and gender variations further demonstrate the uneven salience of religion in electoral mobilization, with northern states and female respondents showing greater susceptibility to clerical endorsements. Godfatherism remains entrenched, often overlapping with religious institutions through reciprocal patronage networks, while widespread practices of vote-buying reflect rational voter strategies under conditions of poverty and weak governance. The study concludes that religion and godfatherism constitute overlapping informal institutions that simultaneously provide electoral legitimacy yet undermine democratic accountability. Recommendations emphasize the need for electoral reforms, strengthened civic education, and inclusive economic policies to mitigate the enduring dominance of informal political structures and foster programmatic competition in Nigeria’s democracy.